Economic evaluation of marketing innovations of the enterprise - Ponomarov, V. D. (WSEH, 2024)
The report determines that industrial enterprises of Ukraine are in a state of crisis, characterized by low labor productivity, reduction of sown areas and unprofitability of industrial production, so it is necessary to intensify their innovative activity. Research work in industry is mainly of an applied nature, their result is new industrial products and technologies for the production of industrial products
Економічна оцінка маркетингових інновацій підприємства
Keywords: economic assessment; varketing innovations; efficiency; market; enterprises